2021
DOI: 10.1037/fam0000805
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the relation between parental functioning and child externalizing behaviors: A meta-analysis on child-driven effects.

Abstract: Guided by multiple theories illustrating the transactional nature of the relation between parents' and children's behaviors, the present meta-analysis provides synthesized evidence on the strength of childdriven effects in eliciting changes in parents' psychological stress and parenting practices. A metaanalysis of 45 independent samples with 640 effect sizes found significant positive associations between children's externalizing behaviors and parents' subsequent functioning (r ϭ .087, 95% CI [.07, .10]). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 51 publications
5
66
2
1
Order By: Relevance
“…A recent meta-analysis found that child externalizing behavior had a small, but significant relationship with later parental psychological distress, controlling for baseline parental functioning (Yan et al, 2021). The effect size for childdriven effects on parents did not significantly differ from parent-driven effects on child externalizing behavior, illustrating the importance of considering the effects of children on their parents (Yan et al, 2021). Contrary to our expectations, child internalizing behavior was not associated with parental COVID-related stress or depression in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…A recent meta-analysis found that child externalizing behavior had a small, but significant relationship with later parental psychological distress, controlling for baseline parental functioning (Yan et al, 2021). The effect size for childdriven effects on parents did not significantly differ from parent-driven effects on child externalizing behavior, illustrating the importance of considering the effects of children on their parents (Yan et al, 2021). Contrary to our expectations, child internalizing behavior was not associated with parental COVID-related stress or depression in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This research also contributes to the growing body of research demonstrating child effects on parental behavior and mental health. A recent meta-analysis found that child externalizing behavior had a small, but significant relationship with later parental psychological distress, controlling for baseline parental functioning (Yan et al, 2021). The effect size for childdriven effects on parents did not significantly differ from parent-driven effects on child externalizing behavior, illustrating the importance of considering the effects of children on their parents (Yan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…People seem to respond to disruption by engaging in rather problematic interaction patterns ( Patterson, 1982 ; Baumrind, 1991 ; Omer, 2011 ; Besnard et al, 2013 ; Tomm et al, 2014 ; Yan et al, 2021 ). PDB has become increasingly problematic during the last decades in this sense, and the central purpose of this article is to account for this recent growth of (c) PDB’s conflict-problematicity.…”
Section: Introductionmentioning
confidence: 99%